2023
DOI: 10.1186/s13034-023-00626-7
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Internet addiction: Does it all begin with their environment?

Khansa Chemnad,
Maryam Aziz,
Azza O. Abdelmoneium
et al.

Abstract: Background This is one of the few studies that examines adolescent Internet addiction (IA) among Middle Eastern population. The purpose of this study is to determine whether adolescents’ family and school environments play a role in their Internet Addiction. Methods We conduced a survey that included 479 adolescents in Qatar. The survey collected demographic data, the Internet Addiction Diagnostic Questionnaire (IADQ), the Brief Family Relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 62 publications
(74 reference statements)
3
14
0
1
Order By: Relevance
“…The study reveals that the students' levels of internet addiction are low while their individual health perceptions are at a medium level. This finding is consistent with the literature (Chemnad et al, 2023) and suggests that internet addiction is a relatively rare problem among university students.…”
Section: Discussionsupporting
confidence: 93%
“…The study reveals that the students' levels of internet addiction are low while their individual health perceptions are at a medium level. This finding is consistent with the literature (Chemnad et al, 2023) and suggests that internet addiction is a relatively rare problem among university students.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the spouse’s internet usage issues can explain the relevant problems among older adults. This study also found that problematic family relationships could be a risk factor for IA among older adults, which is consistent with most other studies [ 47 50 ]. Additionally, this study revealed a new finding that goes beyond traditional research results, suggesting that having a WiFi-covered home environment may increase the risk of IA among older adults.…”
Section: Discussionsupporting
confidence: 93%
“…This finding suggested that the IA behavior of older adults is influenced by their spouse’s internet usage. Similarly, recent research has found that parental IA is a significant predictor of adolescent IA [ 46 , 47 ]. Similar to the role parents play in the lives of adolescents, spouses also play a crucial role in the lives of older adults.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study from Vietnam reported that youth who use internet for socialization and playing games are more susceptible to internet addiction, possibly due to the increased familiarity and entertainment provided through internet use [ 32 ]. Another recent study from Qatar found that family and school environment are associated with internet addiction among adolescents [ 33 ]. These factors are, however, not addressed in our study.…”
Section: Discussionmentioning
confidence: 99%